IMPROVING UNDERBONE MOTORCYLES IGNITION SYSTEM USING CDI PROGRAMMED BY CAMSHAFT DURATION ON A 4-STEP 125 CC MOTOR - Galih Muji Tri Sutrisno; Togik Hidayat (Journal of Engineering, Electrical and Informatics, 2023)
This study aims to determine the engine performance characteristics of underbone motorcycles using Genuine CDI and CDI programmable, as well as the differences in engine performance characteristics of underbone motorcycles using Genuine CDI and CDI programmable. The investigation employed an experimental methodology. The subject of the research was a 125cc, 1-cylinder underbone motorcycles. The apparatus utilized for measuring power was a dynotest underbone motorcycles. Experiments conducted with underbone motorcycles in its standard factory configuration (no modifications). The results indicated that (1) Underbone motorcycles equipped with Genuine CDI produce the most power at 6542 RPM and the most torque at 5085 RPM. While the RPM after it was replaced with Programmable CDI was 8.2 at 6556 RPM with 10.33 lb-ft of torque at 4670 RPM, the maximum power was 8.2 at 6556 RPM. (2) There was a performance difference between Genuine CDI and CDI Programmable. 8,2 HP is the maximum power obtained in nearly all Programmable CDI variantion. By advancing the Programmable CDI Timing by 2 degrees, the maximum torque of 10,33Nm was obtained at 4,670 RPM.